Food, experience and textuality. The advertising of chocolate - Boero, Marianna (E|C, 2020)
This essay proposes an investigation on the theme of taste combining theory and case studies. In the first part of the work the relationship between the concept of taste and the concepts of textuality and experience will be deepened. Taste, in fact, presents itself as a language, as a signifying system capable of communicating cultural values and identities; at the same time, the sense of taste naturally refers to the somatic, perceptive, corporeal dimension, but also to the practices of purchasing / consuming food, in which the experiential dimension has an increasing importance. In the second part of the essay, attention will be focused on advertising, a text that talks about food, to investigate, referring to the Greimasian generative path and its developments, the mechanisms of value investment and narrativization of the gastronomic experience.